Long-term commitment and cooperation - Frédéric Schneider; Roberto A. Weber (University of Zurich, Department of Economics, 2013)
We study how the willingness to enter long-term bilateral relationships affects cooperation even when parties have little information about each other, ex ante, and cooperation is otherwise unenforceable. We experimentally investigate a finitely-repeated Prisoner's Dilemma, allowing players to endogenously select interaction durations. Consistent with prior research, longer interactions facilitate cooperation. However, many individuals avoid long-term commitment, with uncooperative types less likely to commit than conditional cooperators. Endogenously chosen long-term commitment yields higher cooperation rates (98% in one condition) than exogenously imposed commitment. Thus, the willingness to enter into long-term relationships provides a means for fostering - and screening for - efficient cooperation.
Keywords: C72; C92; D03; 330; Repeated games; cooperation; voluntary commitment